RELACIJE ANTROPOMETRIJSKIH KARAKTERISTIKA I KOGNITIVNIH SPOSOBNOSTI SA SITUACIONO-MOTORIČKIM INFORMACIJAMA U KOŠARCI KOD 15-to GODIŠNJAKA - Bećir Šabotić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Today it is known an enormous number of games which regularly organize sport competitions. The most popular of them are included into the program of the Olympic Games, where basketball takes very important place because of its popularity. Basketball is a sport of higher achievement (first-class sport), sport fun as well as the important means of active rest and recovery (of recreation) and of course one of the most powerful means of physical education. The examination is attended to 247 persons who are being examined from the first grade of secondary schools in Novi Pazar, Tutin and Rožaje communities. The goal of the examination was to prove the relation between the set of predictorical variables (anthropometrical characteristics and cognitive capabilities) on one hand and set of variables of criterion of situationally-motorical capabilities in basketball on the other hand. The canonically correlational analyze is being applied for the management of special points. As it was expected, the canonically correlational analyze has shown that there is an important connection between the group of variables for the evaluation of anthropometrical characteristics and cognitive capabilities and the group of variables for the evaluation of situationally-motorical capabilities in basketball. By analyzing the correspondent canonical functions it is being directed at the assumption that the success of the performance of specific motorical movements in basketball at most depends on the longitudinal dimensionality of the skeleton, and from the body mass of the person we are examining. By examining the assumption it is confirmed that the cognitive capabilities influence on the success in overcoming the points in basketball that are given. The author concludes that the person we have examined with given results in anthropometrical characteristics and higher degree of intelligence will achieve better results in specific motorical tests in basketball. These results are logical in consideration of structure when performing the elements in basketball that demand quick moves and good coordination which is directly connected with intelligence. Besides, that given results will have use in order to come to premature selection in sport games, that will say in basketball.